Pengaruh Kompensasi Terhadap Kualitas Pelayanan Publuk (Suatu Studi Di Dinas Kependudukan Dan Catatan Sipil Kabupaten Halmahera Utara) - Hendrik, Rafless; Tulusan, Femmy; Rompas, Sonny (Sam Ratulangi University, 2016)
ABSTRACT : This research was carried out over an alleged that while the quality of public services inthe Department of population and civil registration Kabupoaten of North Halmahera they are still low.Thus, this research aims to find out and analyze the compensation pengaru to the quality of publicservice in the Department of population and civil registration North Halmahera Regency.The methods used in this research is descriptive method quantitative approach. The data andinformation gathered using a questionnaire which was distributed to 33 respondents, engineeringwawawncara and obsrvasi directly to the Office of civil registration and Residency North HalmaheraRegency. After the data is collected and then analyzed using descriptive analysis techniques, namelyportraying the reality of the match is.Research results indicate that the variable compensation is set at